{x2y2+2y2+16=11xyx2+2y2+12y=3xy2 ⇔{2y2=11xy−x2y2−16x2+2y2+12y=3xy2Thế (1) vào (2) ⇒x2+11xy−x2y2−16+12y−3xy2=0⇔x2y2+3xy2−11xy−12y−x2+16=0⇔(x2y2−x2y−4xy)+(3xy2−3xy−12y)+(x2y−xy−4x)+(−4xy+4x+16)=0⇔(xy−x−4)(xy+x+3y−4)=0TH1 xy=x+4, thế vào (2) ⇒x2+2y2+12y=3y(x+4)⇔x2−3xy+2y2=0⇔[x=yx=2yVới x=y thế vào (1) ⇒x4−9x2+16=0 (vô nghiệm)Với x=2y, thế vào (2)$\Rightarrow 6y^3-6y^2-12y=0=0\Leftrightarrow \left[ {\begin{matrix} y=-11\\ y= 2\\y=0\end{matrix}} \right.suyrax rồi thử lại vào Hệ, ta đc 2 nghiệm \begin{cases}x=4 \\ y=2 \end{cases} và \begin{cases}x=-2 \\ y=-1 \end{cases}TH2 xy=4-x-3y thế vào (2)x^2+2y^2+12y=3y(4-x-3y)\Leftrightarrow x^2-3xy+11y^2=0\Leftrightarrow \begin{cases}x=0 \\ y=0 \end{cases}$ thử lại ta thấy khong phải nghiệm của hệ
\begin{cases}x^{2}y^{2}+2y^{2}+16=11xy \\ x^{2}+2y^{2}+12y=3xy^{2} \end{cases} \Leftrightarrow \begin{cases}2y^{2}=11xy -x^2y^2-16\\ x^{2}+2y^{2}+12y=3xy^{2} \end{cases}Thế (1) vào (2)
\Rightarrow x^2+11xy-x^2y^2-16+12y-3xy^2=0\Leftrightarrow x^2y^2+3xy^2-11xy-12y-x^2+16=0\Leftrightarrow (x^2y^2-x^2y-4xy)+(3xy^2-3xy-12y)+(x^2y-xy-4x)+(-4xy+4x+16)=0\Leftrightarrow(xy-x-4)(xy+x+3y-4)=0TH1
xy=x+4, thế vào (2)
\Rightarrow x^2+2y^2+12y=3y(x+4)\Leftrightarrow x^2-3xy+2y^2=0\Leftrightarrow \left[ {\begin{matrix} x=y\\x=2y \end{matrix}} \right.Với
x=y thế vào (1)
\Rightarrow x^4-9x^2+16=0 (vô nghiệm)Với
x=2y, thế vào (2)
\Rightarrow 6y^3-6y^2-12y=0=0\Leftrightarrow \left[ {\begin{matrix} y=-1\\ y= 2\\y=0\end{matrix}} \right.suy ra
x rồi thử lại vào Hệ, ta đc 2 nghiệm
\begin{cases}x=4 \\ y=2 \end{cases} và
\begin{cases}x=-2 \\ y=-1 \end{cases}TH2
xy=4-x-3y thế vào (2)
x^2+2y^2+12y=3y(4-x-3y)\Leftrightarrow x^2-3xy+11y^2=0\Leftrightarrow \begin{cases}x=0 \\ y=0 \end{cases} thử lại ta thấy khong phải nghiệm của hệ